Nigeria and the Classic (2009)
various factor such as diseases, superstitious beliefs, lead poisoning, infanticle, plagues, and much more can be attributed to death in antiquity, people died more from diseases than from the aforementioned factors. Such diseases included fevers (causes, tertian,quartan, and quotidian), tuberculosis, cough, dysentery, tenesmus, diarrhea, brain fever, paroxysms, opthalmia, hemipleghia stranguty, and many more .Of the above named disorders, the fevers which is malaria was the leading cause of death in antiquity. the tertian, quartan, quotidian and the irreglar fevers were frequently mentioned in the works of ancient medical practitioners such as Hippocrates, Aulus cornelius celsus, varro and pliny the Elder some contemporary authors such as david soren and robert sallares through intense reseach unraveled and procnounced plasmodium falciparum (malaria) as the cause of death of children whose bones were excavated in lugnano teverina. This paper however, considers the aforesaid fevers which are malarial in nature as the prinpal cause of death in antiquity.